2009
DOI: 10.1603/029.102.0306
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Susceptibility of Two Banana Cultivars to Banana Bunchy Top Virus Under Laboratory and Field Environments

Abstract: Field and laboratory experiments were carried out on the island of Oahu, HI, to compare the susceptibility of the two most commonly grown banana (Musa sp.) cultivars in the state ('Dwarf Brazilian' or Santa Catarina [locally known as dwarf apple] and 'Williams') to the aphid-borne Banana bunchy top virus (genus Babuvirus, family Nanoviridae, BBTV). Several morphological and physiological features of the two cultivars were monitored to determine whether the banana aphid, Pentalonia nigronervosa Coquerel (Hemipt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…As for the reason underlying this phenomenon, BBTV may adapt banana varieties that include a B genotype. Previous studies have shown that some banana varieties including the B genotype have resistance for BBTV (Hooks et al 2009;Furuya et al 2012). Perhaps, since there may have been some resistant bananas in our sample, the viruses infecting banana varieties including the B type genotype may have greater diversity than those infecting banana varieties including only the A genotype.…”
Section: Genetic Diversity and Selection Pressure In Individual Areasmentioning
confidence: 83%
“…As for the reason underlying this phenomenon, BBTV may adapt banana varieties that include a B genotype. Previous studies have shown that some banana varieties including the B genotype have resistance for BBTV (Hooks et al 2009;Furuya et al 2012). Perhaps, since there may have been some resistant bananas in our sample, the viruses infecting banana varieties including the B type genotype may have greater diversity than those infecting banana varieties including only the A genotype.…”
Section: Genetic Diversity and Selection Pressure In Individual Areasmentioning
confidence: 83%
“…Other studies that have compared laboratory and field results have had mixed findings. For example, Hooks et al (2009) also found a higher transmission efficiency of Banana bunchy top virus by aphids based on laboratory experiments compared to commercial agricultural conditions. Another study that included transmission of Cucumber mosaic virus and Zucchini yellow mosaic virus by multiple aphid species found that the relative transmission rates between field and laboratory conditions depended both on aphid and virus species (Castle et al 1992).…”
Section: Discussionmentioning
confidence: 93%
“…Hooks et al 2009), and there is considerable variation in estimates of transmission efficiency of GLRaV-3 among laboratory studies (Almeida et al 2013). The laboratory and field studies were consistent with each other in that there was no effect of caging the insect vectors on the recipient test vines on virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Although sampling was similar to that described in Robson et al (2006), each leaf position and all plant parts from the bottom to the top of the canopy was inspected for aphids; and sample sites extended beyond the island of Oahu. Aphids are believed to be concentrated in the leaf axis between the petiole and pseudostem (Young and Wright 2005), also referred to as the "throat" of the pseudostem (Hooks et al 2009b). Therefore, the petioles were peeled back and the area within the leaf axes inspected for aphids.…”
Section: Methodsmentioning
confidence: 99%